2000
DOI: 10.3171/jns.2000.92.5.0848
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of postischemic administration of progesterone in spontaneously hypertensive rats with focal cerebral ischemia

Abstract: Administration of progesterone to male rats 2 hours after MCA occlusion reduces ischemic brain damage and improves neurological deficit even 7 days after ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 23 publications
6
68
1
2
Order By: Relevance
“…Altogether, IAD were available for 689 animals. IAD were not shared for six studies in spite of repeated contact with authors; 6,7,12,13,28,29 nevertheless, data from these studies were included in analyses based on summary data. Five studies were excluded, mostly because they did not have data on total lesion volume or vital status, e.g., one study only had data on blood volume collected.…”
Section: Study Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, IAD were available for 689 animals. IAD were not shared for six studies in spite of repeated contact with authors; 6,7,12,13,28,29 nevertheless, data from these studies were included in analyses based on summary data. Five studies were excluded, mostly because they did not have data on total lesion volume or vital status, e.g., one study only had data on blood volume collected.…”
Section: Study Flowmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Progesterone has already been shown to be safe and effective for several clinical applications, e.g., hormone replacement therapy, and a variety of preparations are available for different modes of administration. 15 Furthermore, no severe adverse effects have been reported even when progesterone was used at high dose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of estrogen studies have demonstrated neuroprotection in various ischemia models, two recent papers studying progesterone in stroke models present contrasting results (Kumon et al, 2000;Murphy et al, 2000). Kumon and colleagues (2000) reported an improvement in neurological deficits and reductions in infarct volume with an administration of progesterone as late as 7 days after transient MCAO.…”
Section: Gendermentioning
confidence: 99%
“…Since progesterone acts via a core binding protein and alters DNA transcription, its effect on neurons are accordingly diverse, like upregulating the GABA neurotransmitter, decreasing lipid peroxidation and oxidative stress by its antioxidant effect, limiting the expression of inflammatory cytokines and decreasing cellular apoptosis. All of these, mechanisms result in significantly smaller infarct volumes, smaller extension of edema and altogether better neurologic outcomes on rat models [187][188][189]. Other studies proved that progesterone and its metabolite allopregnanolone inhibit MMP and VEGF upregulation, contributing to BBB maintenance [186].…”
Section: Progesteronementioning
confidence: 99%